Floian, Early Ordovician, trilobites from the Olongbluk Terrane, northwest China - XIN WEI; ZHIQIANG ZHOU (Acta Palaeontologica Polonica, 2023)
Floian, Early Ordovician trilobites are systematically described and revised based on new material from the middle part of the Duoquanshan Formation of the Shihuigou area, northern Qinghai Province, northwest China. The fauna that lived on the shallow-water carbonate platform comprises three species belonging to two families, i.e., Tsaidamaspis diarmatus, Zhiyia tsinghaiensis, and Liexiaspis sp. indeterminate. It exhibits a strong endemicity to the Olongbluk terrane. The new isoteline genus Zhiyia is established on the basis of the material from the Olongbluk terrane and South China palaeoplate, and is characterized by its: (i) almost obsolete cephalic and pygidial axial furrows; (ii) flattened anterior border and narrow (sag., exsag.) occipital ring; (iii) bilobed hypostome with a shallow median notch and a small triangular median projection; (iv) subsemicircular pygidium with wide pygidial axis and border. Faunal evidence indicates that the palaeogeographic position of the Olongbluk terrane may have been situated closer to the South China palaeoplate rather than the North China palaeoplate during the Floian.